Imaging cocaine-induced changes in the mesocorticolimbic dopaminergic system of conscious rats - Febo, Marcelo (2004)
Functional magnetic resonance imaging (fMRI) was used to assess the effects of cocaine on brain activation in fully conscious rats. Methods were developed to image cocaine-induced changes in blood-oxygen-level-dependent (BOLD) signal without the peripheral cardiac and respiratory complications associated with psychostimulant administration. Using spin echo planar imaging (EPI), conscious rats were imaged in a 4.7 T spectrometer prior to and following the intracerebroventricular injection of cocaine (20 μg) in artificial cerebrospinal fluid (10 uL). Within 5 min of injection, there was a significant increase in BOLD signal intensity in the substantia nigra, ventral tegmental area, nucleus accumbens, dorsal striatum and prefrontal cortex, as compared to vehicle controls. Minimal negative BOLD signal changes were observed in response to cocaine and no significant perturbations in normal cardiovascular and respiratory function. These findings demonstrate the technical feasibility of studying psychostimulant-induced brain activity using functional MRI in conscious rats.